Applying trauma systems concepts to humanitarian battlefield care: a qualitative analysis of the Mosul trauma pathway - Kent Garber; Adam L. Kushner; Sherry M. Wren; Paul H. Wise; Paul B. Spiegel (Conflict and Health, 2020)
Abstract Background Trauma systems have been shown to save lives in military and civilian settings, but their use by humanitarians in conflict settings has been more limited. During the Battle of Mosul (October 2016–July 2017), trauma care for injured civilians was provided through a novel approach in which humanitarian actors were organized into a trauma pathway involving echelons of care, a key component of military trauma systems. A better understanding of this approach may help inform trauma care delivery in future humanitarian responses in conflicts. Methodology A qualitative study design was used to examine the Mosul civilian trauma response. From August–December 2017, in-depth semi-structured interviews were conducted with stakeholders (n = 54) representing nearly two dozen organizations that directly participated in or had first-hand knowledge of the response. Source document reviews were also conducted. Responses were analyzed in accordance with a published framework on civilian battlefield trauma systems, focusing on whether the response functioned as an integrated trauma system. Opportunities for improvement were identified. Results The Mosul civilian trauma pathway was implemented as a chain of care for civilian casualties with three successive echelons (trauma stabilization points, field hospitals, and referral hospitals). Coordinated by the World Health Organization, it comprised a variety of actors, including non-governmental organizations, civilian institutions, and at least one private medical company. Stakeholders generally felt that this approach improved access to trauma care for civilians injured near the frontlines compared to what would have been available. Several trauma systems elements such as transportation, data collection, field coordination, and post-operative rehabilitative care might have been further developed to support a more integrated system. Conclusions The Mosul trauma pathway evolved to address critical gaps in trauma care during the Battle of Mosul. It adapted the concept of echelons of care from western military practice to push humanitarian actors closer to the frontlines and improve access to care for injured civilians. Although efforts were made to incorporate some of the integrative components (e.g. evidence-based pre-hospital care, transportation, and data collection) that have enabled recent achievements by military trauma systems, many of these proved difficult to implement in the Mosul context. Further discussion and research are needed to determine how trauma systems insights can be adapted in future humanitarian responses given resource, logistical, and security constraints, as well as to clarify the responsibilities of various actors.